2017
DOI: 10.1002/anie.201705722
|View full text |Cite
|
Sign up to set email alerts
|

The Covalent Functionalization of Layered Black Phosphorus by Nucleophilic Reagents

Abstract: Layered black phosphorus has been attracting great attention due to its interesting material properties which lead to a plethora of proposed applications. Several approaches are demonstrated here for covalent chemical modifications of layered black phosphorus in order to form P-C and P-O-C bonds. Nucleophilic reagents are highly effective for chemical modification of black phosphorus. Further derivatization approaches investigated were based on radical reactions. These reagents are not as effective as nucleoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
122
1
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(138 citation statements)
references
References 42 publications
8
122
1
6
Order By: Relevance
“…The elemental distribution mapping of FL-BP shows the uniform distribution of P and O over the whole nanosheet, indicating the slight oxidation on the surface of FL-BP ( Figure S5d, Supporting Information). [23] In addition, we analyzed the ratio of A A / g 1 g 2 intensity by measuring 70 individual Raman spectra of FL-BP and FL-BP/PFDTS, respectively (inset of Figure 1e). [21] The FL-BP/PFDTS is prepared by dispersing FL-BP in PFDTS DMF solution for 24 h under vigorous stirring at room temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The elemental distribution mapping of FL-BP shows the uniform distribution of P and O over the whole nanosheet, indicating the slight oxidation on the surface of FL-BP ( Figure S5d, Supporting Information). [23] In addition, we analyzed the ratio of A A / g 1 g 2 intensity by measuring 70 individual Raman spectra of FL-BP and FL-BP/PFDTS, respectively (inset of Figure 1e). [21] The FL-BP/PFDTS is prepared by dispersing FL-BP in PFDTS DMF solution for 24 h under vigorous stirring at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…[23,27] Hence, the surface of FL-BP has been oxidized partially during exfoliation. The FTIR of FL-BP shows one weak characteristic band at the position of ≈1631.7 cm −1 2 and ≈669.9 cm −1 , which can be ascribed to the PO stretching vibration and the PO bending vibration respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Sofer et al . have reported that the P−OH groups formed on phosphorene surface due to oxidation can be utilized for functionalization with alkyl halides via the formation of P−O−C bonds . The P−OH groups have been reacted with 1,1,1,2,2,3,3,4,4,5,5,6,6‐tridecafluoro‐8‐iodooctane, 2,3,4,5,6‐pentafluorobenzyl bromide or S‐(bromomethyl) ethanethioate in an argon atmosphere under reflux conditions.…”
Section: Synthesis Structure and Propertymentioning
confidence: 99%
“…Während seine bemerkenswerten physikalischen und Materialeigenschaften bereits intensiv untersucht wurden, bleibt seine Chemie nahezu unerforscht. [18,19] In diesem Sinne wurden bisher nur wenige Arbeiten, wie die Funktionalisierung einzelner Flocken mit Diazoniumsalzen [20] oder die nasschemische Funktionalisierung von zuvor hergestellten Flocken mit Nukleophilen [21][22][23] sowie mit freien Kohlenstoffradikalen, [24] publiziert. [13][14][15][16][17] Abgesehen von diesen Ansätzen gilt die kovalente Funktionalisierung der Oberfläche als eines der vielversprechendsten Konzepte zur Modifizierung der chemischen und physikalischen Eigenschaften von 2D-Nanomaterialien.…”
Section: Seit2014hatderzweidimensionale(2d)schwarzephosphorunclassified
“…[14] Gegenüber anderen aktuellen Berichten über die neutrale kovalente Funktionalisierung von BP mit Diazoniumsalzen [20] oder nukleophilen Molekülen, [21] bei denen keine signifikante Veränderung der Raman-Spektren beobachtet wurde,deuten unsere Ergebnisse auf einen hçheren Funktionalisierungsgrad hin. Vond en auf Si/SiO 2 -Substraten aufgetragenen funktionalisierten BP-Flocken wurden Raman-Karten gemessen, während die Temperatur von 20 auf 220 8 8Cerhçht wurde (Abbildungen 2b und SI 16).…”
Section: Seit2014hatderzweidimensionale(2d)schwarzephosphorunclassified